Reliability of the 36-item version of the Token Test in patients with poststroke aphasia. Issue 5 (October 2015) - Paci, Matteo; Lorenzini, Chiara; Fioravanti, Elena; Poli, Chiara; Lombardi, Bruna
Abstract : Aim: The purpose of this study was to investigate the intra- and inter-rater reliability of the 36-item version of the Token Test. Methods: Twenty-four people following stroke with mild disorder of language comprehension were assessed by two speech therapists at a distance of 2 days apart. Results: The test showed excellent and good inter-rater reliability, while some parts had lower coefficients. Conclusion: This version of the Token Test can be used to assess mild disorder of oral language comprehension. However, further clearer instructions for administration and scoring may improve the test reliability.